HERITABILITY OF FRUIT QUALITY IN THE PROGENIES OF DAY-NEUTRAL AND SHORT DAY HYBRID STRAWBERRY CULTIVARS - Rudi Hari Murti; Hwa Young Kim; Young Rog Yeoung (AGRIVITA, Journal of Agricultural Science, 2012)
This study was conducted to evaluate the heritability, heterosis, and correlation among firmness, total soluble solid (TSS), and color in the F1 hybrids between two day-neutral (DN) and six short-day (SD) cultivars. The firmness of DN cultivars and the sweetness of SD cultivars were considered as a criterion in choosing parent cultivars. Parents and eleven F1 progenies were grown in completely randomized block design. Heritability of TSS, color (a*: opponent channel between red/magenta and green), and firmness was 0.67, 0.55, and 0.49, respectively. Most of the DN × SD hybrids had higher firmness and TSS than the crossing of SD × SD and DN × DN, respectively. In the DN × SD progenies, all heterosis values of TSS and most of heterosis of firmness were positive and negative, respectively. The genetic advance of TSS was higher than firmness. ‘DNKW002’ was a better donor for firmness and can be used as female parent in producing DN cultivar with high TSS. Correlation between firmness and TSS was negative, hence the simultaneous selection was recommended. Principle component analysis (PCA) based on characteristics indicated three groups: group of DN parents and hybrids of DN × DN, group of SD parents and SD × SD hybrids, and group of DN × SD and SD × DN hybrids. Additional key words: firmness, total soluble solid, heritability, PCA